2002
DOI: 10.1093/ansci/80.10.2639
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient database for distiller's dried grains with solubles produced from new ethanol plants in Minnesota and South Dakota

Abstract: A study was conducted to evaluate the nutrient content and variability of distiller's dried grains with solubles (DDGS) originating from new (less than 5 yr old) ethanol plants in Minnesota and South Dakota. Ten plants (8 MN, 2 SD) participated in the study, submitting a total of 118 samples. Samples were collected every 2 mo from ten ethanol plants in the Minnesota-South Dakota (MNSD) region from 1997 to 1999 and were analyzed for amino acid levels, DM, CP, crude fiber, crude fat, ash, ADF, NDF, Ca, P, K, Mg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
149
8
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(192 citation statements)
references
References 4 publications
21
149
8
7
Order By: Relevance
“…Thus, the average values of calcium, phosphorus, copper, iron, manganese and zinc in RDP of present study are increased between 2 and 9 times in comparison with value of brown rice. The results of this study are in agreement with previous studies [4,5,6,21] who indicated that most mineral contents of DDGS are at least 3 times higher than those of the grain from which it originated. In the present study, average phosphorus content in the rice distiller's by-product samples analysed was within the range of published values in DDGS of previous reports [4,5,6,19,20,21].…”
Section: Nutritional Value Of Rice Distiller's By-productssupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, the average values of calcium, phosphorus, copper, iron, manganese and zinc in RDP of present study are increased between 2 and 9 times in comparison with value of brown rice. The results of this study are in agreement with previous studies [4,5,6,21] who indicated that most mineral contents of DDGS are at least 3 times higher than those of the grain from which it originated. In the present study, average phosphorus content in the rice distiller's by-product samples analysed was within the range of published values in DDGS of previous reports [4,5,6,19,20,21].…”
Section: Nutritional Value Of Rice Distiller's By-productssupporting
confidence: 93%
“…The average ash content of RDP (5.15%) was within the range of values (2.2 to 8.5%) in RDP studied by [2]. In this study, NDF level in RDP was high and could provide an advantage in digestive energy and metabolisable energy [4]. When considering fibers, NDF and ADF contents in RDP were higher than that reported by previous work [2] and similar to NDF (34.6%) and ADF (16.3%) values in the DDGS [19].…”
Section: Nutritional Value Of Rice Distiller's By-productssupporting
confidence: 72%
See 3 more Smart Citations